Biotechnology and bioprospecting of Prosopis alpataco from Patagonia, Argentina - Boeri, Patricia Alejandra (2021)
Fil: Piñuel, María Lucrecia. Universidad Nacional de Río Negro, CIT. Río Negro, Argentina.